APPLICATION OF THE THINK TALK WRITE LEARNING MODEL TO IMPROVE THE MATHEMATICAL COMMUNICATION SKILLS OF EIGHTH GRADE STUDENTS - Fikriani, Tiara; Ranti, Sri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2025)
Mathematical communication skills are one of the learning objectives in mathematics that are highly expected to develop and improve. However, in reality, the communication skills of eighth-grade students are low. Based on the observations made, it can be concluded that the learning model used has not been able to activate students in the learning process, resulting in students' mathematical communication skills remaining low. One of learning model that can develop students' mathematical communication skills is the cooperative learning model Think Talk Write (TTW). The purpose of this study is to determine whether the cooperative learning model Think Talk Write (TTW) can improve students' mathematical communication skills. Type of research is experimental with a Randomized Subjects Posttest Only Control Group Design. The population in this study is the eighth-grade students. Based on the results of the research, it can be concluded that The Think Talk Write (TTW) cooperative learning model better than students' mathematical communication skills with conventional learning.